Pendampingan BUMDesa : Peran Strategis Bumdes Dan Revitalisasi Ekonomi Desa Di Kabupaten Karanganyar,Klaten, dan Sukoharjo - Kurniawan, Itok Dwi; Ismawati Septiningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
BUMDes as a village-managed business institution has a strategic role in efforts to improve the village economy. However, unfortunately, there are still very few villages that are able to optimize the role of BUMDes, so that many BUMDes are